العلاقة الوظيفية لمبادئ الصفقات العمومية في التشريع الجزائري - عمراني, مصطفى (جامعة الوادي University of Eloued, 2019)
ملخص: تهدف هذه الدراسة للبحث في مضمون و آلية عمل مبادئ الصفقات العمومية، باعتبارها تسعى إلى تحقيق أهداف مشتركة فيما بينها، و المتمثلة في ضمان نجاعة الطلبات العمومية، و الاستعمال الحسن للمال العام. ومن أجل التأكد من وجود علاقة وظيفية بين المبادئ، أساسها ربط الأهداف الزمنية لمراحل تنفيذ الصفقة العمومية بالمبدأ الموافق بها. نعتمد التقسيم الزمني لمبادئ الصفقات العمومية، و الذي يشكل مفتاح قراءة جديد لكشف العلاقة الوظيفية الحقيقية بين المبادئ. وفي الختام تكشف هذه الدراسة عن وجود علاقة وظيفية للمبادئ، تتفاعل ضمن علاقة متجانسة، وتسعى لتحقيق الأهداف العامة نفسها، وبالتالي تشكل العمود الفقري الحقيقي لقانون الصفقات العمومية Abstract: The purpose of this study is to examine the content and mechanism of the operating principles of public transactions when they seek to achieve common objectives, namely to ensure the effectiveness of public applications and the proper use of public funds. In order to verify the existence of a functional relationship between the principles, the temporal objectives of the stages of the implementation of the public transaction should be linked to the approved principle. In this research, we adopt the temporal division of the basic principles of public transactions, which is the key to a new reading to reveal the true functional relationship between the principles. In conclusion, this study reveals the existence of a functional relationship with the basic principles, which interact in a homogeneous relationship and seek to achieve the same general objectives, constituting the true pillar of the law of public transactions.
Keywords: نجاعة الطلبات العمومية؛ الاستعمال الحسن للمال العام؛ حرية الوصول للطلبات العمومية؛ مبدأ المساواة في معاملة المرشحين؛ شفافية الإجراءات; The effectiveness of public applications; the good use of public funds; the freedom of communication with public applications; the principle of equal treatment of candidates; Transparency of procedures.